Robot‐assisted nerve‐sparing radical cystectomy with bilateral extended pelvic lymph node dissection (PLND) and intracorporeal urinary diversion for bladder cancer: initial experience in 27 cases - Canda, Abdullah E.; Atmaca, Ali F.; Altinova, Serkan; Akbulut, Ziya; Balbay, Mevlana D. (BJU international, 2012)
Study Type – Therapy (case series) Level of Evidence 4 What's known on the subject? and What does the study add? Robot‐assisted (RA) procedures are increasingly being performed as minimally invasive surgical approaches. RA radical cystectomy (RARC) has the advantages of decreased blood loss, decreased time to flatus, decreased time to bowel movement and decreased analgesic use compared with open RC. Positive surgical margin rates and lymph node yields are similar to open RC. RARC was suggested to have the advantage of having fewer complications compared with open RC. To date, very few authors have reported their experience with totally intracorporeal RARC including the urinary diversion. This case series of totally intracorporeal RARC including the urinary diversion reports the operative and postoperative variables, pathological variables, complications, oncological outcomes, functional outcomes and the feasibility of these complex procedures. Advantages of using the surgical robot enable the console surgeon to preserve the neurovascular bundles with excellent surgical oncological safety. Outcomes of the present series suggest that RARC seems to have excellent short‐term surgical and pathological outcomes and satisfactory functional results. Additionally, performing the whole procedure totally intracorporeally might lead to decreased insensible fluid loss from the bowels, which might also prevent development of electrolyte imbalance resulting in earlier bowel function recovery. Additional advantages of this approach include decreased wound infection and dehiscence, better wound healing and better cosmesis. OBJECTIVE • To report the outcomes of 27 patients whom we performed robot‐assisted radical cystoprostatectomy and cystectomy (RARC) with intracorporeal urinary diversion (Studer pouch and ileal conduit) for bladder cancer. PATIENTS AND METHODS • Between December 2009 and December 2010, we performed RARC in 25 men (intrafascial bilateral [22], unilateral [one], non‐neurovascular bundle [NVB] sparing [two]), NVB‐sparing RARC with anterior pelvic exenteration in two women, bilateral extended robot‐assisted pelvic lymph node dissection (RAPLND) (25), intracorporeal Studer pouch (23), ileal conduit (two), and extracorporeal Studer pouch (two) construction. • Patient demographics, operative and postoperative variables, pathological variables, complications (according to modified Clavien system) and functional outcomes were evaluated. RESULTS • The mean (sd, range) operative duration, intraoperative estimated blood loss and mean lymph node (LN) yield were 9.9 (1.4, 7.1–12.4) h, 429 (257, 100–1200) mL and 24.8 (9.2, 8–46), respectively. • The mean (sd, range) hospital stay was 10.5 (6.8, 7–36) days, there was one perioperative death (3.7%), lodge drains were removed at a mean of 11.3 (5.6, 9–35) days and surgical margins were negative in all but one patient who had pT4b disease. • The postoperative pathological stages were: pT0 (five), pTis (one), pT1 (one), pT2a (five), pT2b (three), pT3a (six), pT3b (two), pT4a (three) and pT4b (one). • Positive LNs and incidental prostate cancer were detected in six and nine patients, respectively and at a mean follow‐up of 6.3 (2.9, 1.8–11.3) months, three patients died from metastatic disease and one from cardiac disease. • According to the modified Clavien system, there were nine minor (Grade 1 and 2) and four major (Grade 3–5) complications in the perioperative (0–30 days) period; four minor and three major complications in the postoperative (31–90 days) period. Of the available 18 patients, 11 were fully continent, four had mild and two had severe day‐time incontinence. CONCLUSIONS • Bilateral NVB‐sparing RARC with RAPLND and intracorporeal Studer pouch or ileal conduit reconstruction are complex procedures with acceptable morbidity, excellent short‐term surgical and pathological outcomes and satisfactory functional results. • Studies with more patients and longer follow‐ups are required to evaluate the feasibility of these RA totally intracorporeal complex procedures.